2017
DOI: 10.1080/21501203.2017.1281358
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling and antioxidant as well as anti-bacterial potential of polyphenol producing endophytic fungus-Aspergillus austroafricanus CGJ-B3

Abstract: Fungal endophytes are less studied group of microorganisms with vast therapeutic potential. A polyphenol producing endophyticfungus was isolated from Zingiber officinale rhizome. The ethyl acetate extract of Aspergillus austroafricanus (EAE) was tested against five human pathogenic bacteria by disc diffusion method. Antioxidant activity of EAE was determined by DPPH, H 2 O 2 and nitric oxide radical-scavenging methods. DNA protection from the OH radicals was tested by agarose gel electrophoresis. High-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…As shown in Figure 4, most fermentation experiments produced colored compounds, indicating that the production was affected by the culture media constituents and the evaluation conditions. Thus, the use of PDB promotes the formation of colored compounds in endophytes, as reported by several other studies (Danagoudar et al, 2017;Xu et al, 2018).…”
Section: Primary Screeningsupporting
confidence: 69%
“…As shown in Figure 4, most fermentation experiments produced colored compounds, indicating that the production was affected by the culture media constituents and the evaluation conditions. Thus, the use of PDB promotes the formation of colored compounds in endophytes, as reported by several other studies (Danagoudar et al, 2017;Xu et al, 2018).…”
Section: Primary Screeningsupporting
confidence: 69%
“…It is present in plant seeds and leaves as a component of lignocelluloses, conferring rigidity to the cell wall by making the crosslink between polysaccharides and lignin (45,87). Ferulic acid has been detected in and/or isolated from culture extracts of endophytic fungi like Annulohypoxylon stygium (88) and Aspergillus austroafricanus (89). Ferulic acid has been reported to show several pharmacological activities including antioxidant anti-diabetic, antihypertensive, anticancer, antiinflammatory, hepatoprotective, and antimicrobial activities.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity, the lower the IC 50 value (Pratiwi et al, 2013). A previous study by Danagoudar et al (2017) showed that Aspergillus austroafricanus of Zingiber officinale had an antioxidant activity with an IC 50 value of 82 ± 0.78 µg mg -1 . The IC 50 of the endophytic isolates of Malaysia accessions were expressed in graphical form, as shown in Figure 2.…”
Section: Antioxidant Activity Test With a Uv-vis Spectrophotometermentioning
confidence: 96%